Lynas Industrial Waste – Is It Dangerous - Badhrulhisham, Abdul Aziz (2023)
The safety and environmental issues surrounding the operation of the Lynas plant in Gebeng, Pahang, have once again become a topic of public debate as the time for Lynas’ operating license renewal approaches.